2021
DOI: 10.1186/s13287-021-02673-3
|View full text |Cite
|
Sign up to set email alerts
|

Corneal epithelial differentiation of human pluripotent stem cells generates ABCB5+ and ∆Np63α+ cells with limbal cell characteristics and high wound healing capacity

Abstract: Background Differentiation of functional limbal stem cells (LSCs) from human pluripotent stem cells (hPSCs) is an important objective which can provide novel treatment solutions for patients suffering from limbal stem cell deficiency (LSCD). Yet, further characterization is needed to better evaluate their immunogenicity and regenerative potential before clinical applications. Methods Human PSCs were differentiated towards corneal fate and cryoprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 67 publications
4
18
0
Order By: Relevance
“…Our data show that hiPSC-derived CD200 − ITGB4 + SSEA4 + cells have similar wound healing capacity, melanosome uptake, the ability to form colonies and expression of LEPC markers (CK15, CK19, P-cadherin, CK14, and p63) as T-LEPC [ 14 , 42 , 46 ]. Our data strongly suggest that hiPSC-LEPC are more similar to progenitor and transient amplifying cells than terminally differentiated corneal epithelium and their potential to regenerate the corneal epithelium is similar to the capacity observed in vivo [ 46 , 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 71%
“…Our data show that hiPSC-derived CD200 − ITGB4 + SSEA4 + cells have similar wound healing capacity, melanosome uptake, the ability to form colonies and expression of LEPC markers (CK15, CK19, P-cadherin, CK14, and p63) as T-LEPC [ 14 , 42 , 46 ]. Our data strongly suggest that hiPSC-LEPC are more similar to progenitor and transient amplifying cells than terminally differentiated corneal epithelium and their potential to regenerate the corneal epithelium is similar to the capacity observed in vivo [ 46 , 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 71%
“…Potentially, this cell type could have high regenerative capacity in corneal diseases with stiffened corneal matrix and in wound healing conditions. Indeed, our group has previously demonstrated excellent wound healing capacity of d24 hPSC-LSCs on plastic, [9] which supports the statement that the increased wound healing potential of d24 hPSC-LSCs is dependent of a stiff matrix.…”
Section: Cytoplasmic Yap Correlates With Positive Abcg2 Expressionsupporting
confidence: 77%
“…In our previous studies, we have demonstrated the capability to produce high‐quality hPSC‐LSCs in xeno‐free conditions. [ 9,10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high level of interest in NP based carriers, it was surprising to realize that there are, to our knowledge, no reports describing methods for studying the real-time intake of label-free NP by LSCs and especially with LSCs differentiated from human pluripotent stem cells (hPSC-LSCs) providing novel and highly scalable source of LSCs for regenerative applications. [16][17][18]…”
Section: Introductionmentioning
confidence: 99%